Designing an eco-efficient biomass-based supply chain using a multi-actor optimisation model. (10th February 2019) - Jonkman, Jochem; Kanellopoulos, Argyris; Bloemhof, Jacqueline M.
Abstract: Sustainability concerns emphasise the importance of identifying eco-efficient supply chain configurations which balance economic and environmental chain objectives. The applied modelling approaches for this purpose often assume the availability of raw materials and full coordination within the supply chain studied. Some or all actors in the chain can however pursue individual objectives, making the obtained solutions unfeasible in practice. Economic incentives support aligning the objectives of the different supply chain actors. This paper explores the design of eco-efficient biomass supply chains and economic gain allocation between the supply chain partners. A case study is developed for the sugar beet processing chain in the Netherlands, in which farmers can also choose to produce other competing crops. We observe that higher yields often lead to lower carbon emissions per ton of produce. Hence, eco-efficient solutions are found to have production and processing locations in the most productive regions. Additionally, margin sharing above the minimum sugar beet price is necessary to ensure the production of the desired quantity of sugar beet. Realistic sugar beet prices are determined using a Shapley-value approach, leading to a fair distribution of margin among the farmers and processor in the supply chain. Highlights: We design eco-efficient biomass supply chains using multi-actor optimisation models. Competing crops, production dependent prices, and regional features are considered. We use the sugar beet processing chain in the Netherlands as an example. Fair distribution of benefits is needed to make optimal designs attractive. Locating refineries in regions with productive soils leads to eco-efficient chain designs.